FAKTOR –FAKTOR YANG BERHUBUNGAN DENGAN LAMA PERAWATAN RAWAT INAP PASIEN STROKE DI RUMAH SAKIT ATMA JAYA - Kezia Nathania Limbong Allo; Budi Riyanto Wreksoatmodjo; Poppy Sasmita (NEURONA, 2021)
ABSTRACT Introduction:Stroke patients require a comprehensive treatment at the hospital. At the other hand, length of hospitalization is related to the cost of health care and risk of complication. By understanding more about the contributing factors of length of hospitalization, stroke units candevelop better interventions to reduce prolonged hospitalization and toprevent complications during hospital stay. Aims:This study aims to determine the association between demographic characteristics, comorbidities, complications, type of stroke, severity of stroke, and level of consciousness with length of hospitalization among stroke patients in Atma Jaya Hospital. Method:This cross-sectional study was performed on 254 eligible stroke patients in Atma Jaya Hospital during 2014-2019. Assessment of variables based on secondary data from stroke registry.. Prolonged hospitalization was defined as >7 days. Data analysis was performed using Fisher-exact test, Breslow-Day test, Mantel-Haenzel test, and logistic regression test. Result: From a total of 254 respondents, 65 (25.6%) have a prolonged length of hospitalization. Analysis showed that complications, type of stroke, severity of stroke and level consciousness had a significant association with length of hospitalization. The most influential risk factor on prolonged hospitalization was type of stroke, complication and severity of stroke,. Conclusion: There is a significant relationship between complications, type of stroke, severity of stroke, and level of consciousness with length of hospitalization. Hemorrhagic stroke, patient with severe stroke and complication are the dominant factors for prolonged length of hospitalization in stroke patient.